Juggling the Various Facets of Modern Anatomic Pathology: A Perspective - Pasquale Pisapia; Giancarlo Troncone (MDPI AG, 2023)
Anatomic pathology, along with the role of anatomic pathologists, has significantly evolved over the past several years [...]